Digital Era Dynamics: Uncovering Self-Regulation Patterns in Science Learning Among Border Region Junior High School Students - Luqmanul Hakim Abi Abdillah; Rusdiman Buhera; Agung Wijaya Subiantoro; Shafina Ade Pratiwi; Insih Wilujeng; Laifa Rahmawati (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The research objective is to provide essential insights into students' self-regulation characteristics in border regions, which can inform strategic efforts to maintain and improve their capabilities as they navigate the challenges of the digital era. Methodology: This study used quantitative research with descriptive data analysis involving 198 students from three junior high schools in Nunukan Regency. Data was collected using a self-regulation questionnaire with a Likert scale, which measured four indicators: forethought, volitional control, motivation, and self-reflection. The data was then analyzed using score and average calculations to assess the students' self-regulation profile. Main Findings: The study findings reveal that the self-regulation profile of junior high school students in Nunukan Regency is generally in the high category, with an average of 77%. The motivation indicator reached the highest level at 81%, while volitional control was the lowest at 72%. Notably, differences in self-regulation levels were observed across the participating schools and grade levels. Novelty/Originality of this study: This study provides a comprehensive understanding of the self-regulation characteristics of students in the border area of Nunukan Regency, which can serve as a basis for developing more effective learning strategies and improving the quality of education in similar contexts. The findings offer valuable insights that can inform the development of targeted interventions and support systems to cater to the specific needs of learners in border regions as they navigate the challenges of the digital era.